Screening of Genotoxic Damage in Clones of Bryophyllum daigremontianum (Raym.-Hamet & H. Perrier) A. Berger following Binary Application of Aluminum and Cadmium - ÖZYİĞİT, İBRAHİM İLKER (My University, 2022)
Cadmium (Cd) is one of the most toxic heavy metal and its accumulation causes occurring of serious damages to the environment as well as plant growth. Aluminium (Al) is another phytotoxic metal and its pile-up leads to major agricultural problems in the acidic soils. The present work was performed in order to investigate the impacts of Al and Cd accumulations in the clones of Bryophyllum daigremontianum causing genomic alterations by employing RAPD and ISSR markers that are useful tool for the identification of changes in genetic material. 24 clone plants grown were divided into four separate groups, each including six individuals. Each experimental group was watered with 20 ml Hoagland solution consisting of 0, 50, 100 and 200 μM AlCl3 and CdCl2 that were prepared as mixed applications for 75 days. Sulphuric acid (0.2 %) was applied by being sprayed to all plant soils following each daily irrigation application for providing contribution to create the acidic characteristic (pH 4.8) of the soil structure. At the end of application period, assessments were done to reveal the impacts of Al and Cd accumulations on the uptakes of plant mineral nutrients using the root, stem and leaf samples of the plant by employing ICP-OES. Also, the total protein and photosynthetic pigment contents were analyzed. Furthermore, the alterations in genetic material were determined using RAPD and ISSR markers after the isolation of DNA by CTAB method. Out of 21 RAPD and 19 ISSR primers used, RAPD OPI-19, RAPD OPU16, ISSR UBC 827 and ISSR UBC 857 primers produced reproducible band profiles that were distinguishable in comparisons with the treated and control groups. An increase and a decrease in total protein and photosynthetic pigment contents were obtained, respectively in response to the applications of increased Al and Cd concentrations. Also, new appearances, disappearances and intensity changes in the bands of RAPD and ISSR band profiles were clearly noticed. Our data revealed that as an investigation tool for the observation of genotoxic alterations in plants (especially in clones), the performing of RAPD and ISSR techniques were useful following exposures of Al and Cd. Also, the measurements on other physiological parameters provided correlative results. Finally, it is seen that the plant growth was negatively affected upon following Al and Cd stress applications in dose depending fashion. Keywords: DNA fingerprinting, Genotoxicity, ISSR, RAPD, Kalanchoe
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; DNA fingerprinting; Genotoxicity; ISSR; RAPD; Kalanchoe